PENGARUH MEDIA RODA PUTAR HURUF TERHADAP KETERAMPILAN MEMBACA PERMULAAN SISWA KELAS II SDN TANGGA - Lisnawati; Zulkifli; Sulfahri; Ilyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Beginning reading ability is a fundamental skill that elementary school students need to master as a foundation for acquiring knowledge at higher levels of education. This study aimed to determine the effect of using the letter spinning wheel media on the beginning reading ability of second-grade students at SDN Tangga. The study employed a quantitative approach with a quasi-experimental method using a One Group Pretest–Posttest Design. The sample consisted of 16 second-grade students selected through a saturated sampling technique. Data were collected through tests, observations, and documentation. The data were analyzed using Jamovi software through descriptive statistics, the Shapiro–Wilk normality test, and a Paired Sample t-test. The results showed that the students’ mean score increased from 50.9 in the pretest to 78.8 in the posttest. The hypothesis testing indicated a significant effect of the letter spinning wheel media on students’ beginning reading ability. The improvement was observed in students’ ability to recognize letters, distinguish similar letters, pronounce letters correctly, and combine letters into syllables. Therefore, the letter spinning wheel media can be used as an effective instructional medium to improve beginning reading ability in elementary school students.